Penerapan Model Pembelajaran Improve Pada Materi Nahwu Dalam Meningkatkan Maharoh Qiro’ah Santri PP Darul Lughah Wal Karomah - Wijaya, Mualim (Impressive: Journal of Education, 2023)
Learning in class is often considered a boring and boring experience by students or students. The learning model that is generally used by teachers is the classical and monotonous model, and this often results in difficulties for students in understanding the material presented. This study aims to explain the application of the "Improve" learning model to Nahwu material and evaluate its impact on increasing the qiro'ah spirit in PP Darul Lughah Wal Karomah. This research uses qualitative methods with a case study approach focused on PP Darul Lughah Wal Karomah in Sidomukti Kraksaan Probolinggo and involves the participation of 20 students as respondents. Data collection methods used include observation, interviews, and documentation. The data analysis process we apply is descriptive analysis, which involves the steps of data collection, data condensation, and drawing conclusions. The interim results of this study show that the application of the "Improve" learning model in learning Nahwu Science has had a positive impact. The learning atmosphere in the classroom has changed to be more enthusiastic, and the students find it easier to apply Nahwu's rules in the practice of reading the turast. This research tries to overcome the problem of boring and monotonous learning and offers an effective alternative in increasing the understanding and motivation of learning students in the pesantren environment.